Morpho‐palynological assessment of some species of family Asteraceae and Lamiaceae of District Bannu, Pakistan on the bases of light microscope & scanning electron microscopy. Issue 6 (1st February 2021) - Khan, Siraj; Jan, Gul; Ahmad, Mushtaq; Gul, Farzana; Zafar, Muhammad; Mangi, Jamal Ud Din; Bibi, Hameeda; Sultana, Shazia; Usma, Anwer; Majeed, Salman
Abstract: Pollen micro‐morphological features have proven to be helpful for the plant taxonomists in the identification and classification of plants. The aim of this study was to evaluate the palynological features of family Asteraceae and Lamiaceae from flora of District Bannu, Khyber Pakhtunkhwa, Pakistan using both scanning electron microscopy (SEM) and light microscope (LM) for their taxonomic importance. Pollen of seven Asteraceous species belonging to four genera and four Lamiaceae species categorized into four genera were collected from different localities of research area. The present research work provides detailed information of diverse morpho‐palynological characters both qualitatively and quantitatively including pollen shape, type, diameter, P/E ratio, exine sculpturing and thickness. Type of pollen in Asteraceae and Lamiaceae was ranged from tricolporate, tricolpate, trizonocolpate and hexazonocolpate. The maximum polar diameter (40.05 μm) and equatorial diameter (37.66 μm) was observed in the Ajuga bracteoosa while minimum polar and equatorial diameter was noted in Isodon rugosus (11.10 μm) and Erigeron canadensis (13.20 μm) respectively. Sculpturing of exine include; echinate, reticulate scabrate, aerolate, reticulate–verrucate, reticulate–scabrate, perforate and reticulate to perforate. Exine thickness was examined maximum 1.50 μm in Helianthus tuberosus, whereas minimum in Conyza Canadensis (0.16 μm). The pollen fertility was found highest in C Canadensis (83.33%) and lowest in Ajuga bracteosa (58.06%). The observed pollen morphology has many valuable qualitative and quantitative attributes for the better understanding of their taxonomy and play significant role in correct identification. Abstract : Pollen in unexplored flora of District Bannu was studied with LM and SEM. There is a highly variation in observed pollen micro morphological characters. Pollen morphology has important taxonomic value for the identification of Asteraceous and Lamiaceous species.